Technostress in Motion: How Social Features in Running Apps Trigger Anxiety through Social Comparison - Rony Mohamad Rizal; Akhmad Sobarna; Sumbara Hambali; Silvy Juditya; Diky Komarudin (STKIP Pasundan, 2025)
This study examined how intensity of social feature use in digital running applications (such as Strava) predicts performance-related anxiety among recreational runners, grounded in the technostress framework and social comparison theory. A cross-sectional online survey involving 58 recreational runners in Indonesia assessed social feature usage intensity, social comparison orientation, and performance-related anxiety using validated psychological instruments. Results revealed a significant positive relationship between social feature use and anxiety levels. While social comparison orientation was associated with usage intensity, it did not significantly mediate the relationship with anxiety, likely attributable to limited statistical power from the small sample size. Findings indicate that digital visibility and social comparison pressures within fitness platforms adversely affect users' psychological well-being. In Indonesia's collectivist cultural context, where public image maintenance and peer validation are strongly emphasized, these adverse effects may be substantially amplified.